Design of five two-dimensional Co-metal-organic frameworks for oxygen evolution reaction and dye degradation properties - Fan, Chuanbin; Zhang, Xiaoyin; Guo, Feng; Xing, Zhiyong; Wang, Junli; Lin, Wanying; Tan, Jie; Huang, Guimei; Zong, Ziao (Frontiers in Chemistry, 2022)
Two-dimensional (2D) metal-organic frameworks (MOFs) have been extensively investigated as oxygen evolution reaction (OER) materials because of their numerous advantages such as large specific surface areas, ultrathin thicknesses, well-defined active metal centers, and adjustable pore structures. Five Co-metal-organic frameworks, namely, [Co(L) (4.4′-bbidpe)H2O]n [YMUN 1 (YMUN for Youjiang Medical University for Nationalities)], {[Co2(L)2 (4.4′-bbibp)2]·[Co3(L) (4.4′-bbibp)]·DMAC}n (YMUN 2), [Co(L) (3,5-bip)]n (YMUN 3), [Co(L) (1,4-bimb)]n (YMUN 4), and [Co(L) (4.4′-bidpe)H2O]n (YMUN 5), were designed and fabricated from flexible dicarboxylic acid 1,3-bis(4′-carboxylphenoxy)benzene (H2L) and rigid/flexible imidazole ligands. Their frameworks consist of two-dimensional lamellar networks with a number of differences in their details. Their frameworks are discussed and compared, and their oxygen evolution reaction electrochemical activities and photocatalysis dye degradation properties are investigated.